Effectiveness of Emotionally Focused Couple Therapy on Intimacy, Marital Forgiveness, and Marital Burnout in Women Affected by Extramarital Affairs - Najibzadegan, Arezoo; Bahrainian, Seyed Abdulmajid; Shahabizadeh, Fatemeh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: Extramarital affairs are phenomena that often occur to fulfill an individual's emotional or sexual needs through relationships outside the marital domain. The present study aimed to determine the effectiveness of Emotionally Focused Couple Therapy (EFT) in increasing intimacy and marital forgiveness and reducing marital burnout in women affected by extramarital affairs.Methods and Materials: The present study is a quasi-experimental design with a pre-test, post-test, and follow-up, along with a control group. The statistical population of this study included all women affected by their spouse's extramarital affairs who referred to specialized family counseling centers in District 6 of Mashhad. From this population, 30 women were selected through purposive sampling based on inclusion and exclusion criteria. Data were collected using the Marital Forgiveness Scale by Rye et al. (2001), the Marital Burnout Scale by Pines (1996), and the Marital Intimacy Scale by Thompson and Walker (1983). Participants were randomly assigned to three experimental groups and one control group, each consisting of 15 individuals. Data analysis was performed using repeated measures ANOVA with SPSS-20 statistical software.Findings: The results indicated that Emotionally Focused Couple Therapy was effective in improving intimacy and marital forgiveness and reducing marital burnout in women affected by extramarital affairs (P